2018
DOI: 10.1097/aap.0000000000000798
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block Versus Retrolaminar Block

Abstract: The clinical effect of ESP and retrolaminar blocks can be explained by epidural and neural foraminal spread of local anesthetic. The ESP block produces additional intercostal spread, which may contribute to more extensive analgesia. The implications of these cadaveric observations require confirmation in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(131 citation statements)
references
References 17 publications
(25 reference statements)
3
122
0
6
Order By: Relevance
“…There was potential involvement of the lateral cutaneous branches of the intercostal nerves lateral to the angle of the ribs. Further research is needed to clarify these [21] On the other hand, there has been consistently reported that the ESP block produced additional spread to intercostals spaces over 5 to 9 levels and was associated with a greater extent of craniocaudal spread along the paraspinal muscles such as Adhikary et al demonstrated with cadaveric observations [22]. Despite of this, Chin et al recommend that it makes more sense to perform an ESP block and inject at a vertebral level congruent to the abdominal surgical incision, rather than relying on adequate spread of the LA.…”
Section: Mechanism Of Actionmentioning
confidence: 98%
“…There was potential involvement of the lateral cutaneous branches of the intercostal nerves lateral to the angle of the ribs. Further research is needed to clarify these [21] On the other hand, there has been consistently reported that the ESP block produced additional spread to intercostals spaces over 5 to 9 levels and was associated with a greater extent of craniocaudal spread along the paraspinal muscles such as Adhikary et al demonstrated with cadaveric observations [22]. Despite of this, Chin et al recommend that it makes more sense to perform an ESP block and inject at a vertebral level congruent to the abdominal surgical incision, rather than relying on adequate spread of the LA.…”
Section: Mechanism Of Actionmentioning
confidence: 98%
“…The proposed mechanism of action of the ESPB is via blockade of the dorsal and ventral rami of the spinal nerves. 7,8 Anatomy and imaging studies suggest that the local anesthetic injected into the ESP spreads cranially and caudally as the plane maintains continuity along the spine. Part of the appeal of the ESPB could be that it is easy to implement and gains indirect access to the paravertebral space, and provides analgesia with lower risk for pneumothorax compared with neuraxial block and paravertebral block.…”
Section: Introductionmentioning
confidence: 99%
“…The ESP block has been shown to be able to block the thoracic spinal nerves from Magnetic Resonance Imaging [6]. Nevertheless, this study showed that the ESP block could not provide effective analgesia for 24 hours post-surgery in patients undergoing pneumothorax surgery.…”
Section: Discussionmentioning
confidence: 65%